A streamlined approach for evaluating post-earthquake performance of an electric network. Issue 4 (3rd July 2020) - Sarreshtehdari, Amir; Elhami Khorasani, Negar; Coar, Maxwell
ABSTRACT: Resilience and functionality of a community after an extreme event rely on performance of several interdependent systems. Data from historic events show that power network seems to be the most critical lifeline, given the dependency of water, communication, transportation, and gas networks on power. This paper focuses on modeling of the performance of an electric network, after an earthquake, for application in analysis of interdependent systems. The paper proposes a streamlined approach to analyze post-earthquake performance of an electric network to identify regions in a community without power. The proposed approach quantifies damage at the component level using fragilities and a capacity index parameter that measures operability. System level network analysis, based on the capacity of the network, is completed to measure and compare power flow before and after the earthquake. A limiting ratio is defined to identify dark versus bright regions. The procedure is validated for two case studies.